Business Intelligence in the Vineyard - Neto, M.C. (2008)
The evolution that is nowadays taking place in the information and communication fields, namely in mobile computing and remote monitoring, constitutes a very interesting challenge to the agricultural sector. This reality places agronomic knowledge in centre stage as these technologies are dramatically improving data collection and storage capacities, challenging the farmers and the agricultural field experts to develop processes that efficiently transform data into information and knowledge and are able to support the everyday decision making at farm level. In this work we will present a demonstration project under way in a vineyard in Portugal where we are exploring the potential of the most recent technological innovations available in the market to build the i-Farm, the information and knowledge society intelligent farm. i-Farm (intelligent farm) applies at farm level the potential offered by using in an integrated way mobile solutions, sensor networks, wireless communication and digital imagery materialized in a information system that supports farmer real time decision making in the field and in the office. The i-Farm project creates a unique knowledge repository containing information from multiple sources (crop, environment, soil, operations, market, etc.) enabling accurate and timely decisions. For the project development a Business Intelligence approach is used. In the context of this paper this broad term is used to refer to the process of aggregating, processing and building rich and relevant information which is made available dynamically in real time to managers in an interactive way to support decisions and planning activities